Facile synthesis of silver nanoparticles in a crosslinked polymeric system by in situ reduction method for catalytic reduction of 4-nitroaniline. Issue 15 (3rd July 2019) - Farooqi, Zahoor H.; Khalid, Rida; Begum, Robina; Farooq, Umar; Wu, Qingshi; Wu, Weitai; Ajmal, Muhammad; Irfan, Ahmad; Naseem, Khalida
ABSTRACT: In this study, poly(N-isopropylmethacrylamide-co-methacrylic acid) microgels prepared by free radical precipitation polymerization were used as micro-reactors for the synthesis and stabilization of silver nanoparticles. UV-Visible spectroscopy, Transmission Electron Microscopy and Fourier-transform infrared spectroscopy were used to characterize both pure and hybrid microgels. The catalytic reduction of 4-nitroaniline was carried out in the presence of hybrid microgels to test their catalytic activity, and the catalysis mechanism was explored by varying the concentrations of reacting species like 4-nitroaniline and NaBH4, as well as the dose of the catalyst. The kinetic data indicates that this reaction follows pseudo-first order. The variation in apparent rate constant ( k app ) with respect to NaBH4 concentration also discloses it to be the following Langmuir–Hinshelwood mechanism. The relationship between catalyst concentration and apparent rate constant was found to be increasing in a linear manner. The data obtained also confirmed that silver nanoparticles loaded microgels have the potential to be used as an excellent micro-reactor for selective reduction of 4-nitroaniline to p -phenylenediamine.